Pengaruh Fear Of Missing Out (FOMO) Di Media Sosial Terhadap Kesehatan Keuangan Generasi Z - Moch Diki Yulianto; Monicha Dewi Anggraeni; Alivia Alviasari; Muhammad Adi Wicaksono; Maya Maya; Rahma Amelia; Rama Wijaya Abdul Rozak (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Social media has become a crucial platform for Generation Z to stay updated on the latest trends and access information. The influence of influencers and celebrities on social media often encourages Generation Z to participate in these trends, even if it means compromising their financial stability. This study aimed to investigate the extent to which the fear of missing out (FoMO) affects Generation Z's financial well-being. Using a quantitative approach and comparative causal research method, 101 Generation Z respondents were involved in the study. The analysis revealed that FoMO has a significant impact on Generation Z's financial health, including the use of debt to keep up with the latest trends, which can ultimately lead to serious financial problems. The results showed that the fear of missing out on social media significantly contributes to the financial health of Generation Z, with a regression equation of Y = 39.220 - 0.572 X and a significance value (p) of 0.000 (less than 0.05), indicating that the hypothesis is accepted. In other words, the fear of missing out on social media has a significant negative impact on the financial health of Generation Z, accounting for 48.3% of the financial health of Generation Z